ANALYSIS OF INTERNAL CONTROL OF TRADE RECEIV ABLES FOR NON- AERONAUTICAL SERVICES IN PT. ANGKASA PURA I MANADO - Manueke, Kathleen Arlen; Berhitu, Peggy Indah Jovika; Talimbekas, Juliet Lovely (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
PT Angkasa Pura 1 (Persero) is an airport service company that earns revenue from Aeronautical and Non-Aeronautical services. In this study we will examine the implementation of an internal control system for trade receivables related to money deposited at PT Angkasa Pura 1 Manado Branch. To analyze this problem, we used a descriptive qualitative case study method, using primary and secondary data. The results show that the application of the Internal Control System to trade receivables is not in accordance with the AIS standard. Where, companies should tighten regulations regarding credit payments, and require additional documents for transfer payments. So that transfer errors from tenants can be quickly confirmed, and recording does not need to be done in the Custody Account. Also implementing Virtual Accounts in the future to facilitate transactions and recording in the future.